Detection of antimicrobial residues in bovine meat marketed at Tizi-Ouzou area (Algeria), by a microbial screening assay - TITOUCHE, Yacine; Akkou, M; Houali, K (Journal of the Hellenic Veterinary Medical Society, 2022)
To determine the incidence of antimicrobial residues in bovine meat using a microbiological method, 209 samples of bovine meat (imported: 153; 56 locals: 56) were collected through various retail outlets in Tizi-Ouzou area, Algeria. The collected samples were tested according to the European Union four-plates method (EU4pt), using Bacillus subtilis and Micrococcus luteus ATCC 9341. Only 60 (34/56 local meat and 26/153 imported meat) samples were free from antibiotics residues. Higher prevalence of residues was observed in imported bovine meat (83.01%) than local produced bovine meat (39.29%). High frequencies of contamination for all classes of antibiotics were observed in imported meat rather than local produced meat. From this latter, contamination with β-lactams and/or tetracyclines and sulfonamides was observed in 23.21% and 19.64% respectively. Sulfonamides were the most detected residues in the imported meat with 81.05%. 59.73% of samples were contaminated at least with two families of antibiotics residues, but in proportion that significantly (p<0.05) differ between imported (67.71%) and local produced meat (13.64%). Besides, one antibiotic residue family was detected in most (86.36%) of the contaminated bovine meat produced in Algeria. Our results confirm the non-respect of the withdrawal period between the treatment and slaughter of bovines. For this, further procedures for rational use of antibiotics in livestock and food quality control are required.